Cytotoxic T lymphocytes could contribute in COVID-19-induced passing anosmia - Zaremba, Marcin; Płusa, Agnieszka; Radowicz-Chil , Agnieszka (Medical Studies/Studia Medyczne, 2021)
Several clinical reports have demonstrated a spectrum of neurological manifestations of COVID-19 patients with subsequent post-mortem neuropathological findings. The aim of the case description is to show spotty inflammatory lesions in the olfactory bulb, which could lead to passing anosmia. Microscopic examination showed severe ischaemia and microglial proliferation in the olfactory bulb region. We encountered the presence of perivascular infiltration of cytotoxic T lymphocytes (CD8). The COVID-19 pandemic brought us many new challenges concerning viral detection, transmission, abd spread, then clinical symptoms, and clinical outcome. It seems that cytotoxic T response could be a causative factor not only in respiratory tract injury but also is involved in the neural system, but further studies are required.